Lactoferrin as a regenerative agent: The old-new panacea?. (May 2021) - Antoshin, Artem A.; Shpichka, Anastasia I.; Huang, Guilin; Chen, Kuo; Lu, Pengwei; Svistunov, Andrey A.; Lychagin, Alexey V.; Lipina, Marina M.; Sinelnikov, Mikhail Y.; Reshetov, Igor V.; Timashev, Peter S.
Abstract: Lactoferrin (Lf) possesses various biological properties and therapeutic potentials being a perspective anti-inflammatory, antibacterial, antiviral, antioxidant, antitumor, and immunomodulatory agent. A significant body of literature has also demonstrated that Lf modulates regenerative processes in different anatomical structures, such as bone, cartilage, skin, mucosa, cornea, tendon, vasculature, and adipose tissue. Hence, this review collected and analyzed the data on the regenerative effects of Lf, as well as paid specific attention to their molecular basis. Furthermore, tissue and condition-specific activities of different Lf types as well as problems of their delivery to the targeted organs were discussed. The authors strongly hope that this review will stimulate researchers to focus on the highlighted topics thus accelerating the progress of Lf's wider clinical application. Graphical Abstract: ga1